Некоторые проблемы ресоциализации бывших осужденных - Toma, Marianna; Toma, Marianna (Legea si viata: Publicatie stiintifico-practica., 2019)
The article examines a range of issues related to the process of resocialization of former convicts. Part of the material in the article is devoted to the social and legal concept of the re-socialization of those sentenced to imprisonment and those who have served a sentence of imprisonment. Also, attention is focused on individual factors that hinder the achievement of the goal of correction and re-socialization of convicts.